PENGEMBANGAN MEDIA WORDWALL PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR MATERI AKU DAN LINGKUNGAN SEKITARKU WILAYAH III KECAMATAN TALAWI KOTA SAWAHLUNTO - Tri Amanda Fiska, Dhea; Reinita, Reinita; Bungsu Ladiva, Hasmai; Mansurdin, Mansurdin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a Wordwall learning media for the fifth-grade Pancasila Education subject on the topic Me and My Surrounding Environment in elementary schools that meets the criteria of validity, practicality, and effectiveness. The research was motivated by the limited use of digital learning media in the teaching and learning process. Teachers mainly relied on conventional media such as textbooks and whiteboards, resulting in low student engagement, boredom, and difficulties in understanding the learning materials, despite the availability of supporting facilities such as projectors, laptops, and internet access. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at SDN 15 Kumanis Atas as the trial school and SDN 08 Kumbayau and SDN 14 Kumbayau as the implementation schools. The research instruments included validation sheets completed by material, language, and media experts, practicality questionnaires administered to teachers and students, and pretest-posttest assessments to measure the effectiveness of the developed media. The findings indicated that the Wordwall learning media achieved a validity score of 92.85%, categorized as very valid. The practicality assessment showed that teachers' responses ranged from 94% to 95%, while students' responses ranged from 94% to 99%, all categorized as very practical. Furthermore, the effectiveness test revealed N-Gain scores of 85.7%, 85.02%, and 72%, indicating that the media was highly effective in improving students' learning outcomes. Therefore, the developed Wordwall learning media is valid, practical, and effective for use in fifth-grade Pancasila Education learning in elementary schools